2016
DOI: 10.5935/1806-6690.20160072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pedogenesis of mangrove soils from Ilhéus - BA, Brazil

Abstract: Despite its importance, studies of mangrove soils are scarce, especially from a pedological perspective. The objective of this work was to study the genesis of soils in a mangrove environment in northeastern Brazil (Ilhéus, Bahia) through a morphological, physical, chemical and mineralogical characterization. All soils presented a sandy texture, which is related to the parent material (Quaternary sand deposits). The tidal flooding and resulting hydromorphic conditions is responsible for dominance of dark grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Na > Mg > Ca > K and Cl > SO4 > HCO3. The salts rising in the sediments correlated to the common action of tidal flat, the similar proportions of the ions in the sediment and seawater are due to seawater action (Gomes et al, 2016;Al-Khalf and Al-Saad, 2019). The SO4/Cl indicated that chlorite dominate mineral (Table 4).…”
Section: Iraqi Geological Journalmentioning
confidence: 92%
“…Na > Mg > Ca > K and Cl > SO4 > HCO3. The salts rising in the sediments correlated to the common action of tidal flat, the similar proportions of the ions in the sediment and seawater are due to seawater action (Gomes et al, 2016;Al-Khalf and Al-Saad, 2019). The SO4/Cl indicated that chlorite dominate mineral (Table 4).…”
Section: Iraqi Geological Journalmentioning
confidence: 92%
“…Os materiais sulfídricos são resultantes de áreas encharcadas, acumulados em ambientes permanentemente saturados e geralmente próximos ao litoral. Gomes et al (2016), estudaram os manguezais de Ilhéus-BA, onde todos os solos apresentaram textura arenosa, relacionada ao material de origem. A ação das marés condiciona o hidromorfismo, responsáveis pelo processo de paludização.…”
Section: Horiz a Grossa A Fina Silte Argila Silte/argila ------------unclassified
“…The high OC contents in the Aug horizon may indicate an incipient paludization, a pedogenetic process related to the accumulation of organic matter under anaerobic conditions, which has been widely reported in wetland soils from estuarine ecosystems Gomes et al, 2016;. The high potential of wetlands to accumulate carbon is globally recognized (Macreadie et al, 2019;Nahlik and Fennessy, 2016).…”
Section: Discussionmentioning
confidence: 98%